Listening Learning Design by Using Gagne’s Nine Instructional Events to Trigger Student Learning Communication - Muhammad Syihabul Ihsan Al Haqiqy; Huda, Nurul; Halifah, Nur; Al Haqiqy, M. Sirajuddin (UIN Syekh Wasil Kediri, Indonesia, 2024)
There are learning problems when in the field, not a few students are less enthusiastic and lack response when listening learning activities take place. In this case, learning needs to use strategies in delivering material so that learning outcomes can be achieved efficiently. Therefore, the researcher tried to provide a learning design for listening by using the